From an encyclopedia of Iranian Folklore to an ontology of Iranian folklore - Emadi, Mohsen (2014)
The main resource of the thesis came from 37 years of research work by Ahmad Shamlou, an Iranian poet. The body of research should be transformed from manuscript to digital material. Designing and implementing a semantic ontology for such a folk encyclopedia is a basic and essential part of the thesis. As the material bank is significantly large, semantic marking of the materials in their entirety must be done in a group action and this thesis aims to develop the appropriate framework for the encyclopedia. The model aims to fulfill the philosophy behind Shamlou's approach to the concept of Encyclopedia as an indexical reference to the world by the language and words. The thesis will analyze different approaches in ontology deployment from a basic lexical ontology based on WordNet to an extended model for ontology development involving different domains of knowledge in the field of Folklore. Deploying such model happens in the real conditions surrounding the faith of the remained materials and therefore the digitalization and indexing process must be discussed on pragmatic bases.